How do high ambient temperatures affect infant feeding practices? A prospective cohort study of postpartum women in Bobo-Dioulasso, Burkina Faso - Matthew Chersich; Veronique Filippi; Kadidiatou Kadio; Nathalie Roos; Britt Nakstad; Jenny A Cresswell; Shakoor Hajat; Sari Kovats; Rasmané Ganaba; Adelaide Lusambili; Chérie Part (BMJ Open, 2022)
Objective To examine the effects of high ambient temperature on infant feeding practices and childcare.Design Secondary analysis of quantitative data from a prospective cohort study.Setting Community-based interviews in the commune of Bobo-Dioulasso, Burkina Faso. Exclusive breastfeeding is not widely practised in Burkina Faso.Participants 866 women (1:1 urban:rural) were interviewed over 12 months. Participants were interviewed at three time points: cohort entry (when between 20 weeks’ gestation and 22 weeks’ postpartum), three and nine months thereafter. Retention at nine-month follow-up was 90%. Our secondary analysis focused on postpartum women (n=857).Exposure Daily mean temperature (°C) measured at one weather station in Bobo-Dioulasso. Meteorological data were obtained from publicly available archives (TuTiempo.net).Primary outcome measures Self-reported time spent breastfeeding (minutes/day), exclusive breastfeeding of infants under 6 months (no fluids other than breast milk provided in past 24 hours), supplementary feeding of infants aged 6–12 months (any fluid other than breast milk provided in past 24 hours), time spent caring for children (minutes/day).Results The population experienced year-round high temperatures (daily mean temperature range=22.6°C–33.7°C). Breastfeeding decreased by 2.3 minutes/day (95% CI -4.6 to 0.04, p=0.05), and childcare increased by 0.6 minutes/day (0.06 to 1.2, p=0.03), per 1°C increase in same-day mean temperature. Temperature interacted with infant age to affect breastfeeding duration (p=0.02), with a stronger (negative) association between temperature and breastfeeding as infants aged (0–57 weeks). Odds of exclusive breastfeeding very young infants (0–3 months) tended to decrease as temperature increased (OR=0.88, 0.75 to 1.02, p=0.09). There was no association between temperature and exclusive breastfeeding at 3–6 months or supplementary feeding (6–12 months).Conclusions Women spent considerably less time breastfeeding (~25 minutes/day) during the hottest, compared with coolest, times of the year. Climate change adaptation plans for health should include advice to breastfeeding mothers during periods of high temperature.